Membangun Keunggulan Bersaing Melalui Strategi Umbrella Brand - Prit, Saren; Mulyana, Mumuh (Jurnal Ilmiah Manajemen Kesatuan, 2019)
Business and consumer behavior that is always changing and growing rapidly requires companies to make changes in strategy to increase competitive advantage. The purpose of this study is (1) To determine the strategy of internal and external factors in implementing umbrella brand strategy at PT. Indofood as a competitive advantage. (2) To find out the strategy applied in developing the umbrella brand strategy of PT. Indofood Sukses Makmur as a competitive advantage. The results of this study are (1) Brand that has long been known by the people of Indonesia gets a weight of 0.104 and a rating of 3.8, Brand Image known as a food solution weighs 0.066 and a rating of 3.8, a Brand that has a sufficiently mature strategy is included in the Umbrella brand strategy and excels in competing . (2) PT Indofood's main strengths are brands that have a mature enough strategy, including umbrella brand strategy and excel in competition, Indofood's main weakness is Umbrella Brand (umbrella of many products) which creates confusion among consumers' perceptions of the products number, Indofood's main opportunity is Relationship with stakeholders (communities, retail traders), Indofood's Main Threats are several types of products that have similarities with competitors. (3) Indofood which is in quadrant I position that implements an aggressive strategy using internal strength to take advantage of external opportunities. Keywords : umbrella brand, competitive advantage.